Long-term Functional Results of Total Ankle Arthroplasty in Stiff Ankles. (May 2021) - Brodsky, James W.; Jaffe, David; Pao, Andrew; Vier, David; Taniguchi, Akira; Daoud, Yahya; Coleman, Scott; Scott, Daniel J.
Background: Total ankle arthroplasty (TAA) is advocated over ankle arthrodesis to preserve ankle motion (ROM). Clinical and gait analysis studies have shown significant improvement after TAA. The role and outcomes of TAA in stiff ankles, which have little motion to be preserved, has been the subject of limited investigation. This investigation evaluated the mid- to long-term functional outcomes of TAA in stiff ankles. Methods: A retrospective study of prospectively collected functional gait data in 33 TAA patients at a mean of 7.6 (5-13) years postoperatively used 1-way analysis of variance and multivariate regression analysis to compare among preoperative and postoperative demographic data (age, gender, body mass index, years postsurgery, and diagnosis) and gait parameters according to quartiles of preoperative sagittal ROM. Results: The stiffest ankles had a mean ROM of 7.8 degrees, compared to 14.3 degrees for the middle 2 quartiles, and 21.0 degrees for the most flexible ankles. Patients in the lowest quartile (Q1) also had statistically significantly lower step length, speed, max plantarflexion, and power preoperatively. Postoperatively, they increased step length, speed, max plantarflexion, and ankle power to levels comparable to patients with more flexible ankles preoperatively (Q2, Q3, and Q4). They had the greatest absolute and relative increases in these parameters of any group, but the final total ROM was still statistically significantly the lowest. Conclusion: Preoperative ROM was predictive of overall postoperative gait function at an average of 7.6 (range 5-13) years. Although greater preoperative sagittal ROM predicted greater postoperative ROM, the stiffest ankles showed the greatest percentage increase in ROM. Patients with the stiffest ankles had the greatest absolute and relative improvements in objective function after TAA, as measured by multiple gait parameters. At intermediate- to long-term follow-up, patients with stiff ankles maintained significant functional improvements after TAA. Level of Evidence: Level III, comparative study.